2022
DOI: 10.1002/adma.202270218
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Nature of the Intrinsic Complex Structure of Binary‐Phase Na‐Layered Oxides (Adv. Mater. 29/2022)

Abstract: Electrode Materials In article number 2202137, Kee‐Sun Sohn, Tae Joo Shin, Docheon Ahn, Jun Lu, and co‐workers report an in‐depth phase analysis of their developed Na1−xTMO2 cathode materials with P2‐ and O3‐type phases for Na‐ion rechargeable batteries, providing structural visualization on an atomic scale and unveiling the existence of a mixed‐phase intergrowth layer distribution and unequal distribution of P2 and O3 phases. The synergetic effect of the simultaneous existence of P‐ and O‐type phases and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…A series of P2/O3 mixed‐phase intergrowth layered cathode materials were synthesized by optimizing the Na content (combining P2‐Na 0.7 [Ni 0.20 Fe 0.40 Mn 0.40 ]O 2 and O3‐Na[Ni 0.20 Fe 0.40 Mn 0.40 ]O 2 ). [ 234 ] In‐situ XRD results showed that the optimized biphasic cathode undergoes a reversible phase transition and negligible volume change during cycling, thereby providing high reversible capacity (171.5 mA h g −1 ) and improved cycling stability (64% capacity retention after 100 cycles at 0.1C) over a wide voltage window of 1.5–4.5 V.…”
Section: O3‐tye Layered Oxide Cathodesmentioning
confidence: 99%
“…A series of P2/O3 mixed‐phase intergrowth layered cathode materials were synthesized by optimizing the Na content (combining P2‐Na 0.7 [Ni 0.20 Fe 0.40 Mn 0.40 ]O 2 and O3‐Na[Ni 0.20 Fe 0.40 Mn 0.40 ]O 2 ). [ 234 ] In‐situ XRD results showed that the optimized biphasic cathode undergoes a reversible phase transition and negligible volume change during cycling, thereby providing high reversible capacity (171.5 mA h g −1 ) and improved cycling stability (64% capacity retention after 100 cycles at 0.1C) over a wide voltage window of 1.5–4.5 V.…”
Section: O3‐tye Layered Oxide Cathodesmentioning
confidence: 99%
“…Changing the sodium content has a significant effect on the crystal structure [105,106] . As the sodium content increases, the crystal structure of Na x Ni 0.20 Fe 0.40 Mn 0.40 O 2 changes from a pure P2 phase ( x =0.60) to a composite structure of P2 and O3 phases ( x =0.74, 0.76 and 0.78) and eventually becomes a pure O3 phase ( x =0.84) (Figure 5a).…”
Section: Electrochemical Performancementioning
confidence: 99%
“…As the sodium content increases, the crystal structure of Na x Ni 0.20 Fe 0.40 Mn 0.40 O 2 changes from a pure P2 phase ( x =0.60) to a composite structure of P2 and O3 phases ( x =0.74, 0.76 and 0.78) and eventually becomes a pure O3 phase ( x =0.84) (Figure 5a). [105] The results of HRPD and NDP determine that Na 0.76 Ni 0.20 Fe 0.40 Mn 0.40 O 2 is composed of 18.37 wt% P2‐Na 0.6 [Ni 0.20 Fe 0.40 Mn 0.40 ]O 2 and 81.63 wt% O3‐Na 0.84 [Ni 0.20 Fe 0.40 Mn 0.40 ]O 2 , indicating that the vacancy concentration of the Na ions is not uniform. P2/O3‐Na 0.76 Ni 0.20 Fe 0.40 Mn 0.40 O 2 exhibits an initial discharge capacity of 171.5 mAh g −1 and the capacity retention of 64 % after 100 cycles between 1.5–4.5 V at 0.1 C on the basis of Ni 2+ /Ni 4+ and Fe 3+ /Fe 4+ redox couples (Figure 5b), compared to 118.5 mAh g −1 and 78 % between 2.0–4.2 V. A series of Na 0.9− x Ni 0.45 Mn 0.55 O 2 ( x =0.02, 0.04 and 0.08) with different sodium content were synthesized using the sol‐gel method [106] .…”
Section: Electrochemical Performancementioning
confidence: 99%
See 2 more Smart Citations